اسلامی تاریخی ناول نگاری: نسیم حجازی کے اسلوب کا مطالعہIslamic Historical Novel Writing: A Study of Naseem Hijazi's Style (Al-Qamar, 2021)
Style is a specific identification of any person whether it belongs to some one's outlook or otherwise. Style makes the specifications of personality of the concerned person. Working style of some person makes the recognition of him/her and people know him/her by the specific working style of that person. Likewise, the writing style of every person carries its own specific qualities that make it realize to a reader whose writing this one is.  It becomes easy to understand the meanings of the writer if the reader already knows the qualities of  the writer's style. So I have made an effort to throw a comprehensive beam of light on the writing style of Nasim Hijazi especially in his Islamic Historical Novels. The worth of my research article being presented here is that this is for the first time about the style of Nasim Hijazi that it is being revealed in explanatory way. No one has done any research work like this one. As a result of reading my research paper, any person may get ability to well understand the meaning of Islamic historical novelistic writings of Nasim Hijazi.
Keywords: Writing Style; Specific identification; qualities; Islamic Historical Novel; explanatory way; Understand Meaning; Novelistic writings